Colorful ultralong room temperature phosphorescent afterglow with excitation wavelength dependence based on boric acid matrix - Li, Zhizheng (2024)
Room temperature phosphorescent (RTP) materials have triggered wide interests because of their excellent performance and various promising applications. However, conventional RTP materials possessing color-tunable and ultralong afterglow often suffer from low phosphorescent emission efficiency. Herein, a long lifetime and high-efficiency RTP emission system composed of boric acid as the host matrix and organic phosphors as guest molecules is constructed by suppressing the non-radiative transition process and promoting the triplet exciton of the phosphors. The synergistic effect of the physically limited domain and supramolecular anchoring also contributes to the ultralong lifetime (up to 1.85 s) and high phosphorescence quantum yield (up to 53%). The afterglow can be visually observed for 30 s. With a large overlap of π-conjugated chromophores, the emission peak of RTP redshifted, realizing cyan, green, and red afterglow in the monochromatic domain. In addition, the emission of colorful afterglow and white afterglow is adjustable with the different co-doping ratios. Finally, the application of RTP materials to anti-counterfeiting encryption is demonstrated.